Poli(óxido de etileno-co-dimetilsiloxano) termicamente imobilizado sobre sílica aluminizada como fase estacionária seletiva e estável para CLAE - Santos, Allyson Leandro Rodrigues dos (2019)
Polar compounds usually exhibit low retention, poor resolution and difficulty of separation in reversed phase liquid chromatography and irreversible retention in normal phase liquid chromatography, which have led to several researches in search for solutions to these problems. A recently developed strategy for the efficient analysis of polar compounds has been the use of moderately polar stationary phases, demanding water-rich mobile phases – per-aqueous liquid chromatography (PALC). Due to the low availability of materials with these characteristics and the increasing of new polar molecules in the most diverse industrial areas, this work aimed to develop, characterize and evaluate the applicability of new stationary phase with moderate hydrophilic and chemically stable characteristics, selective to polar compounds. The stationary phase was prepared from the thermal immobilization of poly(ethylene oxide-co-dimethylsiloxane) (PEO) on aluminized silica (SiAl) support. The preparation of the SiAl(PEO) phases was optimized, using a factorial design, requiring a polymer load of 50 % (w/w) of PEO and 135 °C of immobilization temperature, to obtain the best PEO coating of aluminized silica particles. SiAl(PEO) phases were characterized morphologically, structurally and chromatographically by test mixtures already consolidated for the stationary phase characterization. The results of morphological characterization indicated that the SiAl(PEO) phases are composed of spherical particles of high regularity in the size distribution without agglomerations despite the deposition of a monolayer of alumina nanoparticles. The mesoporous particles of SiAl(PEO) presented 374 m2 g-1 of surface area with cylindrical pores of 0.98 cm3 g-1 and diameter of 10.5 nm. Characteristic signals of the PEO, such as the C-O-C stretch at 1050 cm-1, were identified by infrared spectra, as well as the decrease of the band at 980 cm-1 attributed to the vibrations of free silanols groups present on the silica surface. 29Si NMR indicated that the PEO does not form a chemical bond with the support, therefore, it is physically adsorbed on the aluminized silica. SiAl(PEO) phase was applied to mixtures of pesticides and polar drugs, obtaining fast separation with good resolution for all peaks using highly aqueous or alkaline mobile phases, reducing the use of organic solvents in mobile phase. The material presented much higher chemical stability, than chemically bonded commercial phases.